PENGARUH KUALITAS KERJA TERHADAP KINERJA KARYAWAN PT. DUTA PARAMINDO SEJAHTERA - Sulima Dwi Anggarini; Muhammad Muchlas Rowi (SMART Management Journal, 2023)
This study aims to determine whether there is an effect of work quality on employee performance. The method used is a quantitative approach with data collection through a questionnaire. The sample of respondents was taken using a saturated sample technique of 62. The data collection technique used a closed questionnaire or questionnaire with alternative answers using a Likert scale. analysis tool using simple linear regression analysis using t-test. The results of this study are: work quality partially has a positive and significant effect on employee performance. Employee The performance variable can be explained by the variation of the independent variable work quality of 84.5%. While the remaining 15.5% can be explained by other factors or other variables outside variables studied such as work motivation, leadership style, and others